Performativne intervencije v estetskem režimu - Jelesijević, Nenad (Annales. Series historia et sociologia, 2015)
While reflecting on politicisation of aesthetic and aestheticisation of emancipatory potential of art that could lead to its depoliticisation, we discuss two contemporary art performances from Slovenia-Carpeted Assumption (Koper, 2003) and The Burning Cross (Strunjan, 2002). We are indeed interested in practices that act, set up and influence in the aesthetic regime of identifi cation of images, beyond sensory-perceptual dimension of their performances. That criterion follows the premise that the political is a paradigm of the open-that it means a situation in which is enabled entry to whomsoever. We show that the examples converge to, encourage and affirm such situation. Therefore they place themselves into a wider social context of radically shrank space of speech; referring to J. Ranciere we understand speech as a fundamental condition of politics, i.e. embodiment of politics in a specific space of common. The connection between provocation initiated by the performances and their aestheticisation through institutional channels confirms an urge and also effect of critical performative interventions in aesthetic regime. The effect of transaesthetic apparatus of performance that critically intervenes into situations is-at the level of gesture-a rupture with the existing.
Keywords: art; Arts; depolitizacija; Družbena kritika; estetizacija; Govor; performance art; performans; Politics; Politika; Social critique; Speech; Umetnost